1979
DOI: 10.1111/j.1471-0528.1979.tb11237.x
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Pregnancy After Cone Biopsy of the Cervix: A Case‐control Study

Abstract: We investigated the outcome of pregnancy after cone biopsy of the cervix. We found that preterm delivery and low birth weight were commoner and the mean duration of labour longer in women who had a cone biopsy than amongst matched contiwls. Rapid labour (under two hours) was not significantly more common after cone biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(34 citation statements)
references
References 2 publications
3
28
1
2
Order By: Relevance
“…31,38 Only a small number of studies, using an external comparison group, examined the risk of preterm birth associated with spontaneous preterm birth. 11,13,26,36,38 The finding was consistent with that of all preterm birth. The risk associated with more severe outcomes such as extreme prematurity and perinatal morbidity and mortality was not included in this review because of the small number of studies using comparison groups other than an external comparison group; this question has been addressed by another recent review.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…31,38 Only a small number of studies, using an external comparison group, examined the risk of preterm birth associated with spontaneous preterm birth. 11,13,26,36,38 The finding was consistent with that of all preterm birth. The risk associated with more severe outcomes such as extreme prematurity and perinatal morbidity and mortality was not included in this review because of the small number of studies using comparison groups other than an external comparison group; this question has been addressed by another recent review.…”
Section: Discussionsupporting
confidence: 80%
“…When studies examining preterm birth subtypes; preterm prelabour rupture of membranes (pPROM) and spontaneous preterm birth were analysed, the pattern for spontaneous preterm birth, with a pooled relative risk of 1.99 (95% CI 1.68-2.36), 11,13,26,36,38 was similar to that of all preterm birth using an external comparison group. The estimate for the risk of preterm prelabour rupture of membranes was higher, with a wider confidence interval (pooled RR 3.40, 95% CI 1.63-8.11).…”
Section: Association Of Excisional Methods Of Treatment and Preterm Bmentioning
confidence: 99%
“…Early study results show that conization does not constitute a hazard to the outcome of future pregnancies. [8][9][10] However, recent studies have reported that conization can lead to impaired outcomes of pregnancy. [11][12][13] The incidence of preterm deliveries following conization varies in recent publications between 14 and 25%.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical conization, however, is not without significant risk and has been associated with cervical stenosis (13), as well as poor obstetric outcomes. Subsequent pregnancies are at risk of second-trimester pregnancy loss and incompetent cervix (14,15), preterm labor (14), PPROM (16), and preterm delivery (14,(17)(18)(19)(20). Despite the common use of less radical excision procedures, the risk of adverse pregnancy outcomes has been linked, in a number of studies, to LEEP procedures (16,19,21).…”
Section: Discussionmentioning
confidence: 99%